PREPARATION OF PLANT MUCILAGE CLARIFICANTS AND THEIR EFFECT ON JAGGERY PROCESSING OF SUGARCANE VARIETY Co 86032 - Chikkappaiah, Lava; M A, Harish Nayaka; ., Mahadevaiah; G. M., Prashanth Kumar (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The aim of the study was to prepare jaggery from sugarcane variety Co86032 using plants mucilage as clarificants and to determine the effect of plant mucilage on jaggery processing. Methods: Production of jaggery using five plant clarificants namely Aloe vera, Flax seeds, Fenugreek, Purslane and Malabar spinach at three different concentrations i.e., 0.1%, 0.2% and 0.4% of raw sugarcane juice and the jaggery prepared without any clarificants serves as control. During production, the processing parameters such as quantity of scum removed, total time taken for processing and jaggery yield was determined. Results: It was found that the jaggery prepared using plant mucilage at concentration of 0.4% found superior when compared to 0.2%, 0.1% and control respectively. Aloe vera at 0.4% removed maximum scum (4.07%), taken minimum processing time (72.33 min) and recorded maximum jaggery yield (10.92 kg). The efficacy of Aloe vera as mucilage clarificants in jaggery production was followed by fenugreek, flax seeds, purslane and Malabar spinach in the order respectively. Conclusion: The application of plants mucilage as clarificants in the jaggery production removed significant level of scum, reduced processing time and improved yield of jaggery. Therefore the selected plant mucilages can be used as clarificants in the jaggery production and can be considered as potential alternative to chemical clarificants.Â